Training needs for the Madrasati platform from the point of view of principals of general education schools in Al-Kharj Governorate - Almuayli, Nouf Fahad (Journal of Educational and Psychological Sciences, 2025)
This study aims to identify the training needs of male and female principals of general education schools in Al-Kharj Governorate to use the Madrasati platform in the field (technical, vocational) from their point of view. Total population sampling was used for all members of the community, consisting of all principals of general education schools in Al-Kharj, who numbered (144) male principals and (138) female principals, bringing their total to (282) principals. In this study, the researcher prepared a questionnaire to determine the training needs for using the Madrasati platform from the point of view of principals of general education schools in Al-Kharj Governorate. The administrative field came first, then the professional field, and finally the technical field. To conclude that 1- There are a number of training needs in the technical field that concern both male and female principals of general education schools in Al-Kharj Governorate, such as: “knowledge of the regulations, rules, and laws in the Madrasati platform”, 2- There are a number of training needs in the vocational field that concern both male and female principals of general education schools in Al-Kharj Governorate, such as: “It works to assess the level of efficiency of the performance of the platform workers to achieve the goals in the Madrasati platform”, 3- There are a number of training needs in the administrative field that concern both male and female principals of general education schools in Al-Kharj Governorate, such as: “You have a clear vision and goals for the educational process”, 4- There are a number of proposed methods for preparing training programs for using the Madrasati platform, such as: “carrying out field visits to evaluate the use of the Madrasati platform”, 5- There are differences between males and females in the first axis and the three fields, where we find that the differences are in favor of females with a higher average than males in the total degree of the first axis and the three technical, professional, and administrative fields. 6- There are differences between the three academic qualifications in the first axis in its three fields, in favor of the “Ph.D.” educational qualification. 7- There are differences between the numbers of training courses in the first factor in its three fields, in favor of "from one to 3 training courses".
Keywords: Training needs; Technical; Vocational; Administrative; Madrasati platform; Principals of Al-Kharj schools